Contribution of plant anatomy to forensic investigation: Tree bark morphology. (January 2021) - Caccianiga, Marco; Compostella, Chiara; Caccia, Giulia; Cattaneo, Cristina
Highlights: Tree bark is a common botanical element in a crime scene. Bark could be a powerful tool to link a body back to a primary crime scene. Identification keys were prepared for 16 lowland tree species from Northern Italy. Is an identification at the species level from small bark fragments possible? Abstract: Plant science has been more and more utilized in forensic investigation, although its full potential is still to be reached. Plant macroremains are a powerful tool to link a body or other evidence back to a primary crime scene as they can provide detailed information about its previous ecological and geographic location. However, plant macroremains are often poorly preserved and difficult to identify, as diagnostic elements are seldom present within the assemblage occurring on the scene. Plant fragments most likely to be found are those exposed to the environment and resistant to degradation. The bark of woody plants meets these requirements but the possibility of its identification at species level from small fragments is not known. Starting from a real homicide case, where bark splinters were found on the victim, we aimed to assess the forensic potential of bark identification from small fragments like those likely to occur on a crime scene. Two identification keys were prepared for 16 common lowland tree species from Northern Italy; one key used all the available anatomical traits, the second only those from the outer bark. The second key was not able to discriminate some couples of species unambiguously, but could identify the bark fragments of the homicide as Robinia pseudoacacia, as confirmed from direct comparison with a reference sample. Bark fragments deserve to be included into the macroremains to be analyzed during an investigation, but small samples could easily lack diagnostic traits, and the building of a reference collection should be encouraged.